IDENTIFIKASI MISKONSEPSI SISWA DENGAN MENGGUNAKAN THREE TIER MULTIPLE CHOICE DIAGNOSTIC TEST PADA MATERI GERAK DAN GAYA - Safriana Safriana; Ade Irfan (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2021)
This study aims to identify the level of students’ misconceptions on the concepts of motion and force. The research method used is quantitative descriptive research. Sampling using saturated sampling techniques. The sample in this study consisted of 34 students. This misconception will be identified using diagnostic test. The research instrument used was Three Tier Multiple Choice Diagnostic Test. Based on the result of the study, obtained students who have misconceptions on the concepts of motion and force with a percentage rate of misconceptions reaching 49%, the rate of (false positive) misconceptions reaches 7.5%, and the rate of (false negative) misconceptions reaches 8.7%. For the overall level of understanding students guess the category reaches 2.21%, misconception category reached 65.29%, category does not understand the concept reached 19.41%, and know the concept reached 13.08%.